Pengaruh Kebijakan Investasi dan Kebijakan Dividen terhadap Nilai Perusahaan dengan Good Corporate Governance sebagai Pemoderasi (Studi Pada Perusahaan High Dividend 20 yang Terdaftar di BEI 2017-2021) - Evita Setyorini; Muhammad Sulhan (Ekonomis: Journal of Economics and Business, 2023)
In investing, investors wants profit so they make a decision by analyzing the value of the firm. The purpose of this research is to ascertain how investment policy and dividend policy on firm value moderated by GCG. This research used quantitative method with moderating regression analysis (MRA) research method. Investment policy is proxied by TAG, dividend policy ratio through DPR, GCG through ACGS, and firm value through PBV. According to the study’s findings, investment policy have an impact on a firm value although the dividend policy had no bearing. The presence of GCG is able to strengthen the effect of investment policy on firm value but can not affect dividend policy on firm value.